Factors associated with the presence of thrombus in the left atrial appendage and usefulness of the D-Dimer to rule out its presence. (3rd October 2022) - Irigaray Sierra, P; Gayan Ordas, J; Pueo Crespo, E M; Fernandez-Rodriguez, D; Pastor Pueyo, P; Blanco Ponce, E; Matute-Blanco, L; Pueyo Balsells, N; Barriuso Barrado, I; Ramirez Martinez, T; Papiol Morales, E; Worner Diz, F
Abstract: Introduction: A transesophageal echocardiography (TEE) is recommended for non-anticoagulated patients with atrial fibrillation (AF) and >48 hours of evolution requiring electrical cardioversion (ECV) to rule out the presence of thrombus in the left atrial appendage (LAA). It has been proposed that the D-Dimer (DD) value is useful to rule out its presence with high sensitivity and negative predictive value (NPV). Purpose: To evaluate the prevalence of thrombus in LAA in patients with AF, factors associated with its presence and diagnostic accuracy of different DD cut-off points to rule it out. Methods: A retrospective observational study in which patients with AF who underwent a TEE prior to ECV were included consecutively. Results: We included 104 patients (85.6% admitted) between June 2020 and February 2022. In 10 patients (9.6%) thrombus was evidenced in LAA. The mean age was 68.7±11 years and 59.6% were male. Most of the patients had hypertension (64.4%) and 19.2% diabetes. Only 3.8% had had previous stroke. Concerning the echocardiographic findings, the mean left atrial (LA) volume was 56.9±17ml/m 2, LA diameter was 49.2±6.4mm and left ventricular ejection fraction (LVEF) was 47.5±17%. Only 12.5% had a CHADS2VASC2 scale ≤2. 69.2% of patients were not under antithrombotic therapy and only 27% had taken anticoagulant agents before (NOAC or antivitamin K). Neither the CHADS2VASC2 score nor the clinical or echocardiographic factors evaluated were significantly associated with the presence of thrombus (Figure 1). 68 patients had DD available (≤48 hours prior to TEE) and of them 8 (11.7%) had thrombus in the LAA. 12 patients (17%) had DD ≤150ng/mL, 42 (61.7%) DD≤500ng/mL and 48 (80%) DD≤10xAge. Figure 2 shows the ROC curve of the DD: AUC 0.72 (CI 0.55–0.9). NPV to rule out thrombus in LAA was 100% for DD≤150 ng/mL (Sensibility (Se) 100%, Specificity (Sp) 20%), 92% for DD≤500 ng/mL (Se 62.5%, Sp 65%), and 90% for DD≤10xAge (Se 37.5%, Sp 80%). Conclusion: The prevalence of thrombus in LAA in TEE prior to ECV was similar to the previously described. The sample size was insufficient to identify any clinical or echocardiographic factor associated with thrombus. The NPV of a DD≤150ng/mL value was 100%. However, higher cut-off points (500 ng/mL or 10xAge) did not allow to rule out their presence. Funding Acknowledgement: Type of funding sources: None.